2018
DOI: 10.6004/jnccn.2018.7004
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Guideline-Concordant Care Among Older Women With Stage I–III Breast Cancer: A Population-Based Study

Abstract: This study examined receipt of guideline-concordant care (GCC) according to evidence-based treatment guidelines and quality measures and specific types of treatment among older women with breast cancer. A total of 142,433 patients aged ≥66 years diagnosed with stage I-III breast cancer between 2007 and 2011 were identified in the SEER-Medicare linked database. Algorithms considering cancer characteristics and the appropriate course of care as per guidelines versus actual care received determined receipt of GCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
5
19
0
Order By: Relevance
“…Factors associated with treatment noncompliance. In agreement with previous studies, tumor characteristics (pre-surgical tumor size, grade, proxy subtype) and age at diagnosis were associated with initiation of recommended treatment [22][23][24] . Many factors can potentially influence a patient's decision to go along with recommended treatment: previous experiences and personal values 17 , fear of treatment-related side effects 18 , financial ability, age, education and health status, among others 19,20 .…”
Section: Discussionsupporting
confidence: 91%
“…Factors associated with treatment noncompliance. In agreement with previous studies, tumor characteristics (pre-surgical tumor size, grade, proxy subtype) and age at diagnosis were associated with initiation of recommended treatment [22][23][24] . Many factors can potentially influence a patient's decision to go along with recommended treatment: previous experiences and personal values 17 , fear of treatment-related side effects 18 , financial ability, age, education and health status, among others 19,20 .…”
Section: Discussionsupporting
confidence: 91%
“…The most striking difference is observed for breast cancer; 89% of patients aged 65 to 84 years receive surgery compared with just 65% of those aged 85 years and older. Other studies have found that older patients with breast cancer are less likely to receive guideline‐concordant care, even after accounting for patient comorbidities . Moreover, older patients with cancer are not only less likely to receive surgery, but often receive little or no treatment at all .…”
Section: Selected Findingsmentioning
confidence: 99%
“…Previous studies showed that a substantial number of Americans receive less than optimal care . Widespread and equitable access to and utilization of high‐quality care (both preventive and therapeutic) is necessary to achieve the 2035 challenge goal of reducing cancer mortality from the 2015 level.…”
Section: Discussionmentioning
confidence: 99%